Comparison between clinic and home measurements of blood pressure, total cholesterol, blood sugar to identify 10-year atherosclerotic cardiovascular disease risk score - Putri Ani Sunjaya; Agatha Nensida Venary; Ruth Estika Ave Haryono; Rita Suhadi (Universitas Ahmad Dahlan, 2021)
The clinical guideline recommends home monitoring for hypertension, diabetes, and hyperlipidemia maintenance therapy. The study aimed to compare the 10-year atherosclerotic cardiovascular disease (ASCVD) risk calculated using systolic blood pressure, fasting total-cholesterol, and fasting blood sugar measured at the clinic and home. This analytical cross-sectional study was done in population from villages in Sleman District, Yogyakarta. The subjects were selected purposively with the criteria of 40-79 years old and signing the informed consent. The home-measured systolic blood pressure was monitored with a digital sphygmomanometer and peripheral finger-stick methods for cholesterol and blood sugar. On the same occasion, the clinic measurements were monitored with a mercury sphygmomanometer for systolic blood pressure, and with venous plasma analyzed in the laboratory for cholesterol and blood glucose. Measurements between methods were compared with paired T-tests. The subjects (n=171) had a mean age of 52.6 (8.1) years; 21.6% were male. The systolic blood pressure, total cholesterol, and blood glucose from clinic and home measurement were 130.0 (21.1) mmHg and 137.6 (22.4) mmHg (p<0.001); 202.8 (32.8) mg/dl and 205.2 (44.8) mg/dl (p= 0.44); and 98.5 (42.9) mg/dl and 91.9 (34.6) mg/dl (p<0.001) respectively. The average ASCVD risks of the clinic and home measurements were 6.4 (6.2)% and 7.1 (6.9)% (p<0.001); however, both methods had the same ASCVD risk category at borderline risk (5-<7.5%). Conclusion: The ASCVD risk scores calculated using clinic and home measurements were statistically different.